2016
DOI: 10.17222/mit.2014.309
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Zn intermetallic phases prepared by diffusion annealing and spark-plasma sintering

Abstract: The feasibility of iron-zinc intermetallic-phase preparation by spark-plasma sintering (SPS) was investigated. The samples were prepared with a combination of powder metallurgy, where the powder was prepared in evacuated quartz tubes, and a sintering process using SPS. Since the Fe-Zn intermetallic phases are mostly used for hot-dip galvanized steels, the knowledge of the properties of individual intermetallic phases is vital for a better understanding and even further optimization of galvanization processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…XRD patterns showed that the Zn-0.5Fe membrane consists of Zn and FeZn 13 phase, which was matching with the Zn-Fe equilibrium phase diagram [10] and EDS results. The morphology of FeZn 13 phase in the membrane was different from that reported in previous literatures [11], which was caused by membrane produced by powder sintering.…”
Section: Resultscontrasting
confidence: 88%
“…XRD patterns showed that the Zn-0.5Fe membrane consists of Zn and FeZn 13 phase, which was matching with the Zn-Fe equilibrium phase diagram [10] and EDS results. The morphology of FeZn 13 phase in the membrane was different from that reported in previous literatures [11], which was caused by membrane produced by powder sintering.…”
Section: Resultscontrasting
confidence: 88%
“…Generally, there are three phases occurring in the Fe–Zn diagram [ 5 , 6 , 7 ] as a result of the peritectic reaction—Γ-Fe 3 Zn 10 , δ-FeZn 7 , and ζ-FeZn 13 —and an iron solid solution in zinc-η, which settles on the surface as it is pulled out of the bath ( Figure 1 a). There is controversy concerning the order of zinc coating growth.…”
Section: Introductionmentioning
confidence: 99%
“…The presented hardness changes are due to the changes in the microstructure (Г 1 +δ–suggested by results of EDS analysis), caused by diffusion of iron from the steel surface into the coating ( Figure 2 , Table 2 ). The hardness values measured by Pokorny [ 25 ] show that the δ phase is generally about 10% harder than the Г phase; the obtained hardness values of the δ phase were even in the range 330 to 460 HV. According to data [ 16 , 46 ], the δ phase in TD coating is harder by about 15% than the Г phase.…”
Section: Resultsmentioning
confidence: 99%
“… The microstructure of the zinc galvanizing coatings in relation to the Fe-Zn system; ( a )—hot-dip [ 22 ], ( b )—thermal diffusion [ 23 ], ( c )—Fe-Zn equilibrium system [ 24 , 25 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation